Effect of hyperbaric oxygenation on lactate concentration after muscular fatigue from exercise in healthy male : study in 60 naval cadets - Nuntaporn Egtasaeng (Chulalongkorn University, 2007)
Thesis (M.Sc.)--Chulalongkorn University, 2000